Ish: How to Write Poemish (Research) Poetry. (February 2019) - Lahman, Maria K. E.; Richard, Veronica M.; Teman, Eric D.
Discussion has occurred around what constitutes quality research poetry, with some direction on how a researcher, who is a novice poet, might go about writing good enough research poetry. In an effort to increase the existing conversation, the authors review research poetry literature and ideas from art poets on how to read, write, and revise poetry. The authors interrupt the prose text throughout with poetic interludes and quotes from poets. The conversation is framed by the conception of ish and poemish which is drawn directly from Reynolds's powerful book ish . Poemish representations may be said to be research representations characterized by features of poetry and an effort to blend the aesthetics of poetry and science of research into something which may be said to be poem-like, ish, or poemish .